2017
DOI: 10.1016/j.heares.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Efferent modulation of pre-neural and neural distortion products

Abstract: Distortion product otoacoustic emissions (DPOAEs) and distortion product frequency following responses (DPFFRs) are respectively pre-neural and neural measurements associated with cochlear nonlinearity. Because cochlear nonlinearity is putatively linked to outer hair cell electromotility, DPOAEs and DPFFRs may provide complementary measurements of the human medial olivocochlear (MOC) reflex, which directly modulates outer hair cell function. In this study, we first quantified MOC reflex-induced DPOAE inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…An additional revelation from our FFR SWS data was that participants may have benefitted from hearing the F2-F1 distortion product created by the /bO/ stimulus. The F2-F1 frequency is generated by mechanical interaction on the basilar membrane and "feeds forward" into the auditory nervous system, as do other distortion products (Siegel et al, 1982;Chertoff et al, 1992;Dhar et al, 2009;Smith et al, 2017), effectively converting a dynamic two-tone stimulus into a perceptually richer input (Goldstein et al, 1978). Because we did not assess psychophysical weighting of the F2-F1 cue, it is not clear whether its post-training enhancement in the FFR was a consequence of direct attention to this cue or a gross upscaling of any auditory stimuli relevant to the perceptual task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional revelation from our FFR SWS data was that participants may have benefitted from hearing the F2-F1 distortion product created by the /bO/ stimulus. The F2-F1 frequency is generated by mechanical interaction on the basilar membrane and "feeds forward" into the auditory nervous system, as do other distortion products (Siegel et al, 1982;Chertoff et al, 1992;Dhar et al, 2009;Smith et al, 2017), effectively converting a dynamic two-tone stimulus into a perceptually richer input (Goldstein et al, 1978). Because we did not assess psychophysical weighting of the F2-F1 cue, it is not clear whether its post-training enhancement in the FFR was a consequence of direct attention to this cue or a gross upscaling of any auditory stimuli relevant to the perceptual task.…”
Section: Discussionmentioning
confidence: 99%
“…Spectrographic analysis of the average FFR SWS to /bO/ demonstrated that the neural response was in fact phase-locked to the quadratic distortion product (F2-F1) instead of F1. The F2-F1 distortion product is mechanically initiated by interactions between F2 and F1 traveling waves on the basilar membrane, and the nervous system can phase lock to this and other distortions as it would to acoustically-delivered stimuli of the same frequency (e.g., Siegel et al, 1982;Smith et al, 2017). Because F2-F1 is not present in the acoustic stimulus, the neural response does not bear a resemblance to the stimulus.…”
Section: Stimulus-to-response Cross-correlationsmentioning
confidence: 99%
“…As a result, the levels of the 2f1-f2 DPOAE may be even enhanced by MOC activation if MOC efferents suppress one of the component but not the other, depending on their phases [p. 454 in Ref. ( 2 , 89 )]. Because of this, Guinan et al ( 85 ) recommended using stimulus-frequency OAEs (SFOAEs) rather than DPOAEs to assess MOC suppression.…”
Section: Olivocochlear Efferent Effects In Humansmentioning
confidence: 99%
“…This short-latency electrical evoked potential reproduces, as its name implies, the frequencies contained in sustained stimuli as well as, when multi-frequency stimuli are used with appropriate frequency ratios, distortion products of cochlear or even central origin (Pandya and Krishnan, 2004). The FFR is clearly more complex than DPOAEs, since according to the details of the recording technique, it may contain cochlear pre-neural activity, i.e., the pre-synaptic cochlear microphonic (CM; Shaheen et al, 2015), in addition to neural linear and non-linear components (Elsisy and Krishnan, 2008;Smith et al, 2017) generated in different levels of the auditory pathways, from the cochlear nerve to the cortex. Component latencies are logically expected to progressively increase from peripheral to central generators.…”
Section: A the Primary Tone Phase Variation Technique And The Frequementioning
confidence: 99%